Finnish and Iranian teachers' views on their competence to teach purpose. Issue 5 (19th October 2016) - Kuusisto, Elina; Gholami, Khalil; Tirri, Kirsi
Abstract: This paper examines Finnish ( n = 464) and Iranian ( n = 556) teachers' views on their competence to teach purpose. 'Purpose' is defined as a stable intention to accomplish something that is both meaningful to the self and of consequence beyond the self over time. The study revealed that all Iranian teachers evaluated their competence for teaching purpose as being high, regardless of the subject taught. In contrast, among Finnish teachers, there were statistically significant relationships between the subject taught and teachers' self-perceptions: religious education seemed to provide a subject in which Finnish teachers can guide students to consider explicitly their purpose in life and plans for the future, while science and mathematics appeared to offer the most challenging contexts for teaching purpose. Hence, the results challenge Finnish in-service and pre-service teacher education programmes to create new approaches and new cultures for mathematics and science education, which intentionally take into account the moral aspects of teaching. Moreover, regression analysis revealed that teachers' ethical sensitivity predicted their views on teaching purpose in both countries. Results indicate that improving teachers' ethical sensitivity skills in teacher education programmes could provide a significant path for supporting teachers' competence in teaching purpose.